Technical accuracy it is associated with prominence levels in basketball? - Clemente, F. M.; Lourenco Martins, F. M.; Sousa Mendes, R. (Journal of Physical Education and Sport, 2015)
The aim of this study it was verify the association level between technical accuracy and tactical prominence variables of basketball players from different competitive levels. For such analysis, technical accuracy it was analysed using Team Sports Assessment Procedure and tactical prominence using social network analysis metrics. Forty-two basketball players from four different competitive levels (U14, U16, U18 and amateurs with more than 20 years old) it were observed during three official matches. Correlation tests revealed that %inDegree showed a large positive correlation with efficiency index (r = 0.665; p = 0.001) and very large positive correlation with volume of play (r = 0.844; p = 0.001) and performance score (r = 0.843; p = 0.001). The %outDegree showed very large positive correlation with volume of play (r = 0.743; p = 0.001), efficiency index (r = 0.710; p = 0.001) and performance score (r = 0.776; p = 0.001). This study allowed to identify that technical accuracy has great levels of correlation with tactical prominence, mainly in the case of inDegree centrality.